Anatomical substrates and neurocognitive predictors of daily numerical abilities in mild cognitive impairment. (October 2015) - Benavides-Varela, Silvia; Burgio, Francesca; Meneghello, Francesca; De Marco, Matteo; Arcara, Giorgio; Rigon, Jessica; Pilosio, Cristina; Butterworth, Brian; Venneri, Annalena; Semenza, Carlo
Abstract: Patients with mild cognitive impairment experience difficulties in mathematics that affect their functioning in the activities of everyday life. What are the associated anatomical brain changes and the cognitive correlates underlying such deficits? In the present study, 33 patients with Mild Cognitive Impairments (MCI) and 29 cognitively normal controls underwent volumetric MRI, and completed the standardized battery of Numerical Activities of Daily Living (NADL) along with a comprehensive clinical neuropsychological assessment. Group differences were examined on the numerical tasks and volumetric brain measures. The gray (GM) and white matter (WM) volume correlates were also evaluated. The results showed that relative to controls, the MCI group had impairments in number comprehension, transcoding, written operations, and in daily activities involving time estimation and money usage. In the volumetric measures, group differences emerged for the transcoding subtask in the left insula and left superior temporal gyrus. Among MCI patients, number comprehension and formal numerical performance were correlated with volumetric variability in the right middle occipital areas and right frontal gyrus. Money-usage scores showed significant correlations with left mesial frontal cortex, right superior frontal and right superior temporal cortex. Regression models revealed that neuropsychological measures of long-term memory, language, visuo-spatial abilities, and abstract reasoning were predictive of the patients' decline in daily activities. The present findings suggest that early neuropathology in distributed cortical regions of the brain including frontal, temporal and occipital areas leads to a breakdown of cognitive abilities in MCI that impacts on numerical daily functioning. The findings have implications for diagnosis, clinical and domestic care of patients with MCI.